The Degree of Practice Educational Islamic Methods by Secondary School Teachers from Male and Female Students Viewpoints in Taif - Alqethami, Mikhlid Srih (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the degree of secondary school teachers’ practice of Islamic educational methods in Taif. To achieve the objectives of the study, a questionnaire consisting of (42) items was built and developed, covering five areas: Method of Education in (good example, the story, proverbs, reward and punishment, dialogue). The validity and reliability were verified, and the study sample was (500) male and female students. The most important results of the study the degree of secondary school teachers’ practice of Islamic educational methods in Taif is moderate in all areas with a total mean of (3.35). The researcher recommends holding training courses for male and female teachers to use and enhance Islamic educational methods in the educational process and sensitize them to the positive effects of using Islamic educational methods in order to raise the degree of practice of these methods.